(untitled) (Revista Nacional de Odontología, 2020)
Introduction. The most recent approaches to health communication refer to the importance of conceiving social groups as protagonists of the transformations related to their quality of life and the recognition of social interaction as the central axis in community processes oriented to change. This article describes the multidisciplinary process of construction of a communication project for oral health guided by an interactive ludic educational tool, aimed at families belonging to an educational center for children in Usaquén, Bogotá. Method. The study was developped with a group of 18 families using a methodology of participatory action research based in workshop strategies an focus groups. Resoults. A strategy mediated by ICT was designed and implemented, materialized in a mobile application that includes a game with a nighttime routine connected to an electronic dummy, as well as a focused story in values and three educational infographics in oral health. Conclusions. As a result, this resource is expected to generate an impact on learning for the adoption of practices that promote oral self-care, where ICT helps the development of innovative learning activities with a didactic and motivational potential.